PENGARUH PERSEPSI HARGA, KUALITAS LAYANAN DAN DISPLAY PRODUK TERHADAP KEPUTUSAN KONSUMEN DALAM MEMBELI PRODUK TELEVISI (Studi pada Transmart Wilayah Jabodetabek) - Bahtiar, Firman Adam; Harwani, Yuli (Universitas Mercu Buana, 2024)
This study aims to determine and analyze the effect of price perception, service quality, and product display on television product purchasing decisions. The population of this research is Transmart consumers in the Greater Jakarta area who shop for television, with a sample of 105 respondents based on the Hair Method. The design of this research is descriptive, with a quantitative approach in associative form. Collecting data using a survey method with the research instrument is a questionnaire. The data is processed using Partial Least Square (PLS) version 3.0. Based on the measurement and structural tests that perception of price and service quality, each has a positive and significant effect on consumer decisions to buy television products at Transmart, while product displays have a positive but not significant effect. Theoretically, this research is expected to be able to contribute in increasing scientific knowledge. And practically the researchers hope that the results of this study can be used as a reference in determining the company's strategic policies to improve sales performance.